Olax scandens Mediated Biogenic Synthesis of Ag-Cu Nanocomposites: Potential Against Inhibition of Drug-Resistant Microbes - Mujeeb, Anzar Abdul; Khan, Nuha Abeer; Jamal, Fauzia; Badre Alam, Khan Farheen; Saeed, Haris; Kazmi, Shadab; Alshameri, Ansam Wadia Faid; Kashif, Mohammad; Ghazi, Irfan; Owais, Mohammad (Frontiers in Chemistry, 2020)
In the present study, we have synthesized Silver-Copper nanocomposites (Ag-Cu NCs) using Olax scandens leaf extract (green synthesis method) and evaluated their antimicrobial potential against less susceptible pathogens. The kinetics of Ag-Cu NCs synthesis was followed by UV-VIS and fluorescence spectroscopy. The physicochemical characterization of as-synthesized Ag-Cu NCs was executed using electron microscopy, Energy Dispersive X-Ray, Fourier Transform Infrared Spectroscopy and Differential Light Scattering method. As-synthesized Ag-Cu NCs induce formation of Reactive Oxygen Species (ROS), thereby causing alteration and decrementation of cellular proteins, DNA, lipids etc., and eventually leading to cell death as determined Live/Dead assay. Next, we assessed anti-biofilm potential of as-synthesized Ag-Cu NCs against biofilm forming bacteria. The as-synthesized Ag-Cu NCs, when compared to monometallic silver nanoparticles, exhibit significantly higher anti-microbial activity against both sensitive as well as drug resistant microbial isolates.